STATIC VERSUS PNF STRETCHING IN HAMSTRING FLEXIBILITY-A COMPARATIVE STUDY (International Journal of Physiotherapy, 2015)
Background: Stretching used as a technique for injury prevention in the clinical settings, the study aimedto determine the early findings of hamstring tightness with both groups in the population, now a daysthe sedentary activities like prolonged sitting might cause hamstring tightness and change in pathkinematics of gait intern lead to postural defects and back pain, understanding of the stretching helpsclinician to make decisions for rehabilitation.Methods: Across-sectional study, counterbalanced with repeated-measures , one group with staticstretch – (double hamstring stretch and hurdlers stretch) for 3 times,30seconds subsequently in anothergroup PNF contract relax(agonist contraction) technique for 10 seconds position and 10 seconds stretchrepeated for 3 times.Results: The results from data and statistical analysis by using t-test, SPSS obtained by using goniometerare tabulated in terms of mean, standard deviation and p-value in both groups. In experimental groupflexion with PNF showed improvement 9.27±1.91(right side), 9.53±2.42(left side) and static stretchingshowed 7.8±2.91(right side), 7.47±1.96(left side) this proves that PNF has consistent improvement thanstatic stretchingConclusions: Static and proprioceptive neuromuscular facilitation stretching both have produced greaterimprovement but compared with PNF contract relax(agonist) stretching showed significant change inhamstring flexibility compared with control group . The effect sizes, however corresponding to thesestretching-induced changes were small, which suggests the need for practitioners to consider a risk-tobenefit ratio when incorporating static or proprioceptive neuromuscular facilitation stretching.